Rhizophora Apiculata As Eco-Friendly Inhibitor Against Mild Steel Corrosion in 1 M HCL - Asaad, M.A. (World Scientific Publishing Co. Pte Ltd, 2017)
The inhibitive characteristics of aqueous extracts from mangrove (Rhizophora apiculata) bark and leaf on the corrosion of mild steel (MS) coupon in 1 M HCl were examined by means of the gravimetric measurement (weight loss), electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization techniques. The MS surface morphologie were investigated using field emission scanning electron microscopy (FESEM) with Energy Dispersive X-Ray Analysis (EDX) at 120h in the presence and absence of green inhibitors in corrosive medium. Respective inhibition efficiencies of 68.1 and 59.0 were obtained when exposed to 10 v/v Rhizophora apiculata solution for 72h. Examination of the adsorption behavior of the solutions indicated the Langmuir isotherm model as being the most likely relevant adsorption mechanism. In addition, polarization measurements showed that both bark and leaves extract inhibitors act via mixed type inhibition. © 2017 World Scientific Publishing Company.